Alitretinoin in treatment of chronic hand eczema – mechanism of action - Matejko, Maria; Kręcisz, Beata (Dermatology Review/Przegląd Dermatologiczny, 2016)
Hand eczema is a common skin disorder with significant functional and economic impacts. Conventional therapy options, such as topical corticosteroids, calcineurin inhibitors, phototherapy and systemic immunosuppressants, often give unsatisfactory results, due to lack of efficacy or predominant adverse effects. Alitretinoin (9-cis-retinoic acid) is an active substance from the group of retinoids and is licensed as a systemic drug for chronic and severe hand eczema refractory to topical treatment. It binds with high affinity to both retinoic acid receptor (RAR) and retinoid X receptor (RXR) receptors and presents anti-inflammatory and immunomodulatory activity. Due to its good tolerance and high efficacy, demonstrated in several large clinical studies, alitretinoin may be an option for patients with severe chronic hand eczema refractory to other treatment.